IDENTIFIKASI INTERAKSI OBAT-OBAT POTENSIAL PADA PASIEN GAGAL GINJAL KRONIK RSPAD GATOT SOEBROTO - maifitrianti maifitrianti (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2016)
Drug interactions are directly related to factors such as polypharmacy, aging, hepatic metabolism and decreased renal function. Polypharmacy is common in drug prescriptions of chronic kidney disease patients. A study of the prescription patterns of drugs with potential interactions would be of interest to prevent drug related adverse events. The aim of this study was to identify potential drug-drug interactions among chronic kidney disease among hospitalized patients in Gatot Soebroto Army Hospital, Jakarta period October to December 2015 This study was an observational research with descriptive approach. Data were obtained retrospectively. Data was collected from patient’s medical record. The sampels were hospitalized patients with chronic kidney disease in Gatot Soebroto Army Hospital, Jakarta period October to December 2015 that received at least two drugs in one prescribing pattern. The samples which fulfilled the inclusion criteria were 63 patients and found as many as 443 potential drug interactions. Drug interactions with pharmacodynamic mechanism were 235 cases (53.04%) and pharmacokinetics as much as 208 cases (46.96%). A total of 334 cases (75.39%) were drug interactions with moderate severity. drug interactions are commonly seen in the prescriptions of chronic kidney disease patients which can lead to serious adverse events if not detected early.